HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA DENGAN KEIKUTSERTAAN PERAWATAN PASIEN STROKE - Muhammad Irwan (Ensiklopedia of Journal, 2021)
Stroke is the number 3 cause of death after heart disease and cancer in the elderly group and the number 1 cause of disability worldwide as well as the leading cause of death in hospitals. A factor that can lead to stroke treatment that is not maximal is the lack of family knowledge. The purpose of this study is to find out the relationship of knowledge and family attitudes with the participation of stroke patient care. This research uses a cross sectional approach. Research sampling technique uses accidental sampling with a sample families accompanying patients in hospital care of 30 people. Data collection tool in this study using questionnaires that have been done validity and realization tests. From the results of the Statistical Test family knowledge with the participation in stroke patient care obtained a value of p=0.03 which means it is smaller than α=0.05. Thus, it can be concluded that there is a meaningful relationship between family knowledge and the participation in stroke patient care. From the results of the Statistical Test family attitudes with the participation in stroke patient care obtained a value of p=0.01 which means it is smaller than α=0.05. Thus, it can be concluded that there is a meaningful relationship between family attitudes and the participation in stroke patient care. The relationship between family knowledge and attitudes and the participation in stroke patient care. It is recommended for families with low knowledge to always improve information about stroke care and it is expected to health workers to always provide health education for families with low knowledge so that the information obtained can be known properly and correctly.